2020
DOI: 10.1177/1757177420976813
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic usage and stewardship in patients with COVID-19: too much antibiotic in uncharted waters?

Abstract: Background: Antimicrobial usage and stewardship programmes during COVID-19 have been poorly studied. Prescribing practice varies despite national guidelines, and there is concern that stewardship principles have suffered. Aim: To analyse antibiotic prescriptions during the COVID-19 pandemic at a teaching hospital and to propose improved approaches to stewardship. Methods: We reviewed COVID-19 admissions to medical wards and intensive care units (ICUs) in a London teaching hospital to assess initial antibiotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 25 publications
0
9
0
4
Order By: Relevance
“…Evans et al reported that overall mortality in ICU patients with COVID-19 under mechanical ventilation at the St George’s Hospital, London, was 35%. Most of ICU patients did not have bronchoalveolar lavages undertaken, and therefore bacterial coinfections in this study were not evaluated [ 27 ]. Based on Yang et al study, the mortality rate was 32 cases in 37 critically ill patients with COVID-19 documented mechanical ventilation.…”
Section: Discussionmentioning
confidence: 99%
“…Evans et al reported that overall mortality in ICU patients with COVID-19 under mechanical ventilation at the St George’s Hospital, London, was 35%. Most of ICU patients did not have bronchoalveolar lavages undertaken, and therefore bacterial coinfections in this study were not evaluated [ 27 ]. Based on Yang et al study, the mortality rate was 32 cases in 37 critically ill patients with COVID-19 documented mechanical ventilation.…”
Section: Discussionmentioning
confidence: 99%
“…Other hospital ASPs have shown that they could discontinue or narrow antibiotics for CAP in patients with COVID-19 within 72 hours of admission. 33,34 This finding contrasts with a report by Cong et al, 32 who reviewed 118 publications and stratified patients with COVID-19 into mild-to-moderate or severe-to-critical illness categories. Antibiotic prescribing during the first 6 months of the COVID-19 pandemic was high (>75%) in both groups.…”
Section: Discussionmentioning
confidence: 75%
“…To assess this possibility, we refit the model on a subcohort that excluded recommendations for ID consults (results unshown), and receipt of an ID consult remained strongly protective against intervention (aOR, 0.58 [95% CI, .53–.64]). Third, our cohort preceded the COVID-19 pandemic, which precipitated important changes in inpatient antimicrobial prescribing [ 23–26 ]. It is unclear how our models would generalize to periods of high COVID-19 inpatient volumes, and whether optimal models would require COVID-19-specific predictors.…”
Section: Discussionmentioning
confidence: 99%